Identification of Human using Palm-Vein Images: A new trend in biometrics (International Journal of Engineering and Computer Science, 2017)
In the ubiquitous network society people faced with the risk that others can easily access their information anytime and anywhere. Because of this risk, personal identification technology, which can distinguish between registered legitimate users and imposters, is now generating interest Traditional personal verification methods rely heavily on the use of passwords, personal identification numbers (PINs), magnetic cards, keys, smart cards, etc. No matter which method is employed, each of these offers only limited security. To solve these problems, biometric authentication technology, which identifies people by their unique biological information, is attracting attention